Searching for Emma : Gustave Flaubert and Madame Bovary - Maraini, Dacia (University of Chicago Press, 1998)
Although many writers blend autobiography and fiction, few have been so forthright in admitting it as Gustave Flaubert. Reflecting on his legendary novel and protagonist, he wrote: "Madame Bovary, c'est moi." Emma Bovary has become an icon for casual readers and feminists alike, but, as Dacia Maraini argues, she is one of the most problematic, though fascinating, female protagonists in modern literature.